1995
DOI: 10.1136/bmj.310.6993.1498
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effect of sucrose in full term infants: a randomised controlled trial

Abstract: Concentrated sucrose solution seems to reduce crying and the autonomic effects of a painful procedure in healthy normal babies. Sucrose may be a useful and safe analgesic for minor procedures in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
113
1
7

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 13 publications
11
113
1
7
Order By: Relevance
“…This shows that 25% and 50% glucose when given orally are comparable in their analgesic effect and 10% glucose and EBM have a comparable analgesic effect. Our results are similar to the results of Blass et al [5], Haouari et al [6] and Ramenghi et al [7], the only difference being that all these studies had used sucrose solutions for analgesic.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This shows that 25% and 50% glucose when given orally are comparable in their analgesic effect and 10% glucose and EBM have a comparable analgesic effect. Our results are similar to the results of Blass et al [5], Haouari et al [6] and Ramenghi et al [7], the only difference being that all these studies had used sucrose solutions for analgesic.…”
Section: Discussionsupporting
confidence: 92%
“…In a similar study by Skogsdal et al [12], in neonates with more than 30 weeks gestation and of age between 24 hours and 30 days, mean duration of 1 st cry was found to be 35 seconds in neonates given no treatment, while it was 10 seconds in neonates given 25% glucose. In another study Haouari et al [6], using oral sucrose as an analgesic agent, found decrease in duration of 1 st cry in neonates given 12.5%. 25% and 50% solutions, which are comparable with our study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Sixteen of the 29 articles selected were studies of fullterm neonate patient samples, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] eleven studied preterm neonates [33][34][35][36][37][38][39][40][41][42][43] and two included comparisons between preterm and fullterm neonates. 44,45 The volume of sucrose used in the majority of the studies involving fullterm neonates was 2 ml, [17][18][19][20][21][22][23][24][25][27][28][29][30][31][32] with concentrations of 12%, 20,24,30,31 12.5%, 18,32 24%, …”
Section: Resultsmentioning
confidence: 99%